Low Frequency Oscillations and Bifurcation Diagram in Semi-Insulating GaAs Samples - A.G. de Oliveira (Brazilian Journal of Physics, 2006)
We present an experimental study of bifurcation diagrams from low frequency current oscillations (LFO) measurementsobtained from semi-insulating GaAs samples grown by low temperature molecular beam Epitaxy (LTMBE).The considered growth temperatures were 215 ° C and 265 ° C. LFO are considered to be spontaneouslygenerated oscillations under constant applied bias V. These oscillations were measurement and recorded in theform of time series. The bifurcation diagrams were obtained from the sequence of minima as a function of theapplied bias. The standard measurement procedure was described elsewhere. As the control parameter, the biasallows the identification of a bifurcation route to chaos.